Development of staff scheduling system for preschool / Nur Syuhadah Ghazali - Ghazali, Nur Syuhadah (2014)
The aim of this research project is to develop staff scheduling system for preschool based on the categories of staff and the working hours. Based on the interview conducted with the stakeholder, the main problem is to allocate the task among the staff which is full time staff and part time staff .The working hours between the full and part time staff is different in the preschool. The working hours and qualification of staff are the constraint to create the schedule. There are three objectives to be accomplish in this project. The first objective is to gather the requirement of staff scheduling system in preschool. Secondly is to design the staff scheduling system for preschool and lastly to develop and demonstrate the staff scheduling system for the preschooL Based on the research, there are several techniques to solve the scheduling problem. There are also has solution to generate rotation schedule. It is important because the schedule should generate in automation schedule on weekly basis with the constraint mention before. Besides, the comparison of existing system give better understanding what the best features needs to be exist in the project. Through this project, iterative model approach is implemented to develop the system. Iterative model is where the continuity of each phases can be redo each time until development. The requirement can change throughout the phases. This project is developed to provide efficient and useful schedule system to generate schedule on weekly basis to the staff and the principal in the future use.